Rayon Grade Pulp from Poplar - Rai, Anoop Kumar; Chand, Ilam; Garhia, Rajesh (Indian Forester, 1995)
Populus deltoides 'G-3' wood chips were prehydrolysed with water and delignifed by sulphate process using 16-18% total chemicals and keeping the sulphidity 25% at 165Â°C temperature, for a period of three hours. The unbleached pulps were bleached using multistage CEHHD sequence. The bleached pulps were chemically analysed for alpha cellulose (94.90-95.03%), beta cellulose (4.23-4.27%) and gamma cellulose (0.74-0.83%). The copper number, ash content, intrinsic viscosity and inorganic matters were determined. The pulps in 30.5-33.8% yield and of satisfactory brightness were obtained. The chemical analyses of pulp show that rayon grade pulp of high alpha cellulose, low inorganic matter and satisfactory intrinsic viscosity could be prepared from Populus deltoides 'G-3' and the results are comparable with standard specifications of rayon grade pulp.